Coal-based hard carbon negative electrode sodium storage material as well as preparation method and application thereof

By combining alkali activation method and ball milling method to treat anthracite, the microcrystal size is reduced and the closed-cell structure is formed, the problem of low efficiency of hard carbon anode materials is solved for the first time, high energy density and good circulation performance are achieved, and commercial Demand.

CN119176544AActive Publication Date: 2024-12-24CHINA UNIV OF GEOSCIENCES (WUHAN)

Patent Information

Application Number
CN202411348617.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-24
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The first-time Coulomb efficiency of existing hard carbon anode materials in sodium ion batteries is low and cannot meet the commercial requirements. Especially the first-term effect of anthracite-based hard carbon after activation treatment is low and cannot meet the needs of high energy density.

Method used

The alkali activation method and ball milling method are combined to treat the anthracite precursor through ball milling to reduce its crystal crystal size, and the formation of closed-cell structure is regulated during the high-temperature carbonization process to improve the first Coulomb efficiency of hard carbon.

Benefits of technology

After the ball milling treatment, the first Coulomb efficiency of the hard carbon material reached more than 90%, meeting commercial demands, and good circulation performance. The capacity retention rate after 300 cycles is as high as 90.3%, proving that the ball milling process is in improving the performance of hard carbon material Validity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176544A_ABST
    Figure CN119176544A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a coal-based hard carbon negative electrode sodium storage material and a preparation method and application thereof. The preparation method comprises the following steps: S1, activating anthracite serving as a base material by adopting an alkali activation method to obtain activated anthracite; s2, carrying out ball milling on the activated anthracite to obtain an anthracite precursor with a small microcrystalline size; and S3, performing high-temperature carbonization on the anthracite precursor to obtain the coal-based hard carbon negative electrode sodium storage material. An alkali activation method and a ball milling method are combined to prepare the anthracite-based hard carbon, the alkali activation method can effectively remove ash of coal and activate the anthracite, so that the anthracite can be carbonized into the hard carbon, the ball milling method can effectively reduce the crystallite size of the activated anthracite, and in the high-temperature carbonization process, the carbon content of the anthracite is reduced. The cross-linking effect between oxygen-containing functional groups is promoted, so that a large number of closed pores are formed, the closed pore structure limits the electrolyte from entering the pores, irreversible loss in first circulation is reduced, and the first coulombic efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a coal-based hard carbon negative electrode sodium storage material and a preparation method and application thereof. Background Art

[0002] There are still bottlenecks in the industrialization of sodium-ion batteries, among which the negative electrode material is a key link restricting industrialization. At present, hard carbon is the most commercially promising negative electrode material for sodium-ion batteries, but it faces the severe challenge of low first coulombic efficiency, which limits the energy density of the battery. Among the many hard carbon precursors, biomass (such as coconut shells, walnut shells, etc.) has poor batch consistency and low carbon content; polymers are expensive and monomers are usually toxic; and anthracite has the advantages of high carbon content, low ash content, and large reserves, and has attracted much attention. However, anthracite has a soft carbon structure after pyrolysis, and activation treatment is required to obtain hard carbon. However, the first efficiency of anthracite-based hard carbon treated only by activation is low and cannot meet commercial requirements (>90%). Therefore, a simple, clean and low-loss method is urgently needed to further improve the first efficiency of hard carbon. Summary of the invention

[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and propose a coal-based hard carbon negative electrode sodium storage material and its preparation method and application. The present invention uses anthracite as a precursor, reduces the crystallite size of the anthracite precursor by ball milling, regulates the formation of a closed-pore structure during high-temperature carbonization, and effectively improves the first coulombic efficiency of hard carbon.

[0004] A method for preparing a coal-based hard carbon negative electrode sodium storage material of the present invention comprises the following steps:

[0005] S1. Using anthracite as a base material, activating it by an alkali activation method to obtain activated anthracite;

[0006] S2, ball-milling the activated anthracite to obtain an anthracite precursor having a small crystallite size;

[0007] S3. Carbonize the anthracite precursor at high temperature to obtain a coal-based hard carbon negative electrode sodium storage material.

[0008] Furthermore, the anthracite precursor La obtained in step S2 is 14-16 nm, and Lc is 0.8-0.95 nm.

[0009] Furthermore, the specific operation of step S1 is: fully mixing and grinding the anthracite with a strong alkali, then transferring the powder to air or nitrogen for pre-pyrolysis, and grinding the pre-pyrolysis product, then acid washing, water washing, suction filtering, and drying to obtain activated anthracite.

[0010] Furthermore, step S1 also includes oxidizing the activated anthracite.

[0011] Furthermore, the oxidation treatment operation is to heat the activated anthracite in air.

[0012] Furthermore, the strong base includes one or more of sodium hydroxide and potassium hydroxide.

[0013] Furthermore, the pre-pyrolysis temperature is 200-400°C; and\or: the pre-pyrolysis temperature is 400°C.

[0014] Furthermore, the pickling is performed by stirring and immersing in hydrochloric acid or sulfuric acid with a concentration of 1 to 6 mol / L; and washing with water until the pH is neutral.

[0015] Furthermore, in step S2, the ball milling is wet milling, with a rotation speed of 300 to 800 r / min, lasting for 4 to 12 hours, and a ball-to-material ratio of 200:1.

[0016] Furthermore, in step S3, the temperature of high temperature carbonization is 1000-2000°C, the time is 1-10 hours, and the heating rate is 1-5°C / min.

[0017] A coal-based hard carbon negative electrode sodium storage material prepared by the above-mentioned preparation method.

[0018] An application of the coal-based hard carbon negative electrode sodium storage material as described above is used as a negative electrode material for a sodium ion battery.

[0019] The present invention adopts a combination of an alkali activation method and a ball milling method to prepare anthracite-based hard carbon. The alkali activation method can effectively remove the ash of coal and activate the anthracite, so that the anthracite can be carbonized into hard carbon. The ball milling method effectively reduces the crystallite size of the activated anthracite and controls the crystallite size La of the anthracite to be 14-16nm and Lc to be 0.8-0.95nm. During the high-temperature carbonization process, the cross-linking effect between oxygen-containing functional groups is promoted to form a large number of closed pores. The closed pore structure restricts the electrolyte from entering the pores, reduces the irreversible loss in the first cycle, and thus improves the first coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart of the preparation method of the present invention;

[0021] Figure 2 The XRD diagrams of the precursors of each embodiment and the anthracite precursor of Comparative Example 1;

[0022] Figure 3 The Raman spectra of the precursors of each embodiment and the anthracite precursor of Comparative Example 1;

[0023] Figure 4 are the crystallite parameters of the precursors of each embodiment and the anthracite precursor of Comparative Example 1;

[0024] Figure 5This is the first cycle charge and discharge curve diagram of Example 1;

[0025] Figure 6 This is the cycle performance diagram of Example 1. DETAILED DESCRIPTION

[0026] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0027] Example 1

[0028] Step 1: Grind 1.5 g of anthracite and 3.0 g of potassium hydroxide in an agate mortar, then transfer the powder to a muffle furnace for pre-pyrolysis at a temperature of 400 °C and a heating rate of 5 °C / min. Grind the pre-pyrolysis product into powder using an agate mortar, soak it in 200 mL of 3 mol / L hydrochloric acid for pickling for 2 h, then wash it with a large amount of deionized water until the pH is neutral, and finally obtain the activated anthracite after filtration and drying.

[0029] Step 2: ball mill the activated anthracite obtained in step 1 at a rotation speed of 500 r / min for 4 h, with a ball-to-material ratio of 200:1, add 20 mL of ethanol for wet grinding, and obtain an anthracite precursor with a small crystallite size after drying.

[0030] Step 3: Transfer the anthracite with small microcrystal size obtained in step 2 to a high-temperature tubular furnace, and calcine it at 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere to obtain a high-initial-efficiency sodium-ion battery hard carbon negative electrode material.

[0031] Example 2

[0032] Step 1 is the same as in Example 1.

[0033] Step 2: ball mill the activated anthracite obtained in step 1 at a rotation speed of 500 r / min for 12 h, with a ball-to-material ratio of 200:1, add 20 mL of ethanol for wet grinding, and obtain an anthracite precursor with a small crystallite size after drying.

[0034] Step three is the same as in Example 1.

[0035] Example 3

[0036] Step 1: Same as Example 1.

[0037] Step 2: ball mill the activated anthracite obtained in step 1 at a speed of 500 r / min for 4 hours, with a ball-to-material ratio of 200:1, add 20 mL of ethanol for wet grinding, and obtain an anthracite precursor with a small crystallite size after drying. The anthracite precursor is oxidized by heating it to 400°C in a muffle furnace for 2 hours and oxidizing it with air. Finally, an anthracite precursor with a small crystallite size rich in oxygen-containing functional groups is obtained.

[0038] Step 4: Transfer the oxidized small-crystal-sized anthracite obtained in step 3 to a high-temperature tube furnace and calcine it at 1400°C at a heating rate of 2°C / min to obtain a high-initial-efficiency sodium-ion battery hard carbon negative electrode material.

[0039] Comparative Example 1

[0040] Different from Example 1, Comparative Example 1 was not subjected to the second step of ball milling.

[0041] 1.5 g of anthracite and 3.0 g of potassium hydroxide were thoroughly ground in an agate mortar, and then the powder was transferred to a muffle furnace for pre-pyrolysis at a temperature of 400 °C and a heating rate of 5 °C / min. The pre-pyrolysis product was fully ground into powder using an agate mortar, and then soaked in 200 mL of 3 mol / L hydrochloric acid for pickling for 2 h, followed by washing with a large amount of deionized water until the pH was neutral, and finally filtered and dried to obtain the activated anthracite precursor.

[0042] The activated anthracite precursor was transferred to a high-temperature tube furnace and calcined at 1400°C at a heating rate of 2°C / min to obtain a hard carbon negative electrode material for sodium ion batteries.

[0043] Comparative Example 2

[0044] Step 1 is the same as in Example 1.

[0045] Step 2: ball mill the activated anthracite obtained in step 1 at a rotation speed of 500 r / min for 20 h, a ball-to-material ratio of 200:1, add 20 mL of ethanol for wet grinding, and obtain an anthracite precursor with a small crystallite size after drying.

[0046] Step three is the same as in Example 1.

[0047] Comparative Example 3

[0048] Step 1 is the same as in Example 1.

[0049] Step 2: ball mill the activated anthracite obtained in step 1 at a rotation speed of 500 r / min for 28 h, a ball-to-material ratio of 200:1, add 20 mL of ethanol for wet grinding, and obtain an anthracite precursor with a small crystallite size after drying.

[0050] Step three is the same as in Example 1.

[0051] Comparative Example 4

[0052] Step 1: Same as Example 1.

[0053] Step 2: The activated anthracite obtained in step 1 is subjected to oxidation treatment, and the process is to place it in a muffle furnace, heat it to 400° C. and maintain it for 2 hours, and oxidize it with air. Finally, an activated anthracite precursor with rich oxygen-containing functional groups is obtained.

[0054] Step 4: Transfer the oxidized anthracite precursor to a high-temperature tube furnace and calcine it at 1400°C at a heating rate of 2°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0055] Electrode sheet preparation and battery assembly:

[0056] The electrochemical properties of hard carbon were tested by assembling a 2032 model half-cell. For slurry preparation, aqueous binders sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) were selected, and the materials with a mass ratio of hard carbon: conductive carbon black: CMC: SBR = 90:2:3:5 were weighed, mixed thoroughly with pure water and evenly coated on copper foil, and then transferred to a vacuum oven at 80°C for drying for 12 hours. After that, circular electrode sheets with a diameter of 12 mm were cut to assemble button cells, in which sodium metal was the counter electrode, the diaphragm was glass fiber (Whatman GF / D), and the electrolyte used an ether electrolyte 1M NaPF6 in DIGLYME = 100 Vol%. The oxygen and moisture contents in the glove box were both less than 0.1 ppm, and the test current was 0.3C (defined as 300 mAg -1 =1C), the test voltage range is 0.001~3V.

[0057] Table 1 shows the values ​​of the crystallite parameters La and Lc of each embodiment and comparative example, and Table 2 shows the electrochemical performance of each embodiment and comparative example 1 obtained by the above-mentioned assembly test.

[0058] Table 1 Crystallite size of anthracite precursor

[0059] Precursor Precursor ball milling time / h La / nm Lc / nm Example 1 Precursor 4 14.40 0.91 Example 2 Precursor 12 14.11 0.88 Example 3 Precursor 4 14.51 0.94 Comparative Example 1 Precursor 0 16.02 1.00 Comparative Example 2 Precursor 20 12.95 0.84 Comparative Example 3 Precursor 28 11.98 0.81 Comparative Example 4 Precursor 0 15.89 0.98

[0060] Table 2 Electrochemical properties of samples

[0061] sample First coulombic efficiency / % Specific capacity / mAh g1 Platform specific capacity / mAh g1 Example 1 92.2 263.0 191.0 Example 2 91.0 263.6 194.7 Example 3 93.2 288.3 212.0 Comparative Example 1 84.4 249.4 180.2 Comparative Example 2 80.7 184.2 140.0 Comparative Example 3 79.2 179.0 135.5 Comparative Example 4 83.6 264.1 191.2

[0062] It can be seen from Table 1 that as the ball milling time increases to 28 h, the lateral crystallite size La decreases from 16.02 nm to 11.98 nm, but the stacking height Lc does not change significantly, only decreasing from 1.0 nm to 0.81 nm. Therefore, ball milling mainly reduces the lateral crystallite size La.

[0063] It can be seen from Table 2 that when the ball milling time is not more than 12h (i.e. La>14.11nm), the first coulombic efficiency reaches more than 90%, meeting the commercialization requirements (>90%). However, when the ball milling time is greater than 12h (i.e. La<14.11nm), the first coulombic efficiency and capacity both drop significantly, and most of the capacity loss comes from the platform area. Since the platform area capacity of hard carbon during the sodium storage process is mainly contributed by the closed-pore structure, it indirectly shows that too long ball milling time will reduce the closed-pore volume in hard carbon. This is because during the high-temperature calcination process, the pinning effect caused by the too small crystallite size of the precursor will hinder the rearrangement of carbon atoms and the movement of carbon layers, which is not conducive to the evolution of closed pores. Correspondingly, the excessively large crystallite size of the precursor makes it difficult for oxygen-containing functional groups (such as -COOH and C=O) to cross-link, which is not conducive to the induction of the formation of closed pores.

[0064] Figure 1 The flow chart of the present invention is shown in FIG. 1. Taking Example 1 as an example, the hard carbon with high initial efficiency is finally obtained through three steps: KOH activation, ball milling, and high-temperature calcination.

[0065] Figure 2 1 is the XRD spectrum of each embodiment and comparative example. It can be seen that the broadening of the (002) peak of each sample is not obvious, indicating that the stacking height Lc does not change significantly. After fitting calculation, it can be known that the Lc of the ball milling time of 0, 4, 12, 20 and 28h is 1.00, 0.91, 0.88, 0.84 and 0.81nm respectively.

[0066] Figure 3 is the Raman spectrum of each embodiment and comparative example, wherein the peak area ratio A of the D peak to the G peak is D / A G It can not only indicate the degree of defects, but also calculate the lateral crystallite size La. After fitting calculation, it can be seen that the Lc of ball milling time of 0, 4, 12, 20 and 28h is 16.02, 14.40, 14.11, 12.95 and 11.98nm respectively. Therefore, the ball milling process significantly reduces the lateral crystallite size La of the anthracite precursor.

[0067] Figure 5 This is the first cycle charge-discharge curve of Example 1. It can be seen that the hard carbon has an obvious low potential platform area (<0.1V), indicating the existence of a closed-pore sodium storage mechanism. The platform capacity is 190.3mAh g -1 , accounting for 72.4% of the total capacity, indicating that the sodium storage capacity is mainly contributed by closed pores. Figure 6 This is the cycle performance diagram of Example 1. After 300 cycles, the capacity retention rate is as high as 90.3%, indicating that the closed-cell structure has good cyclability.

[0068] The ball milling process can improve the first Coulombic efficiency of hard carbon materials. The principle is that the crystallite size of the anthracite precursor is reduced after ball milling. The smaller crystallite size promotes the cross-linking between oxygen-containing functional groups (such as -COOH and C=O) during the calcination process. This process induces the generation of a large number of closed microporous structures. Since the closed-pore structure restricts the electrolyte from entering the pores to form SEI, the irreversible decomposition of the electrolyte is effectively reduced, thereby improving the first Coulombic efficiency of hard carbon materials. However, if the precursor crystallite size is too small, it will hinder the movement of the carbon layer, which is not conducive to the evolution and generation of closed pores.

[0069] Comparative Examples 1 and 4 show that the first efficiency cannot be improved by oxidation treatment alone. This may be because the additionally introduced oxygen-containing functional groups are difficult to carry out more cross-linking in the precursor with a larger crystallite size, so there is almost no improvement.

[0070] Example 3 shows that after introducing additional oxygen-containing functional groups, reducing the crystallite size has a certain improvement on the initial efficiency and capacity. This is because the oxidation treatment further increases the oxygen-containing functional groups, so that there are more sufficient oxygen-containing functional groups in the anthracite precursor to provide cross-linking. However, based on the current performance data, in actual production, only one step of ball milling is required to reduce the crystallite size of the anthracite precursor.

[0071] In summary, the anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1 of the present invention has a rich closed microporous structure and its first charge capacity is 263.2 mAh g -1 , the first coulombic efficiency is as high as 92.2%, the cycle performance is good, and the capacity retention rate after 300 cycles is 90.3%. The strategy provided by the present invention to reduce the size of the anthracite precursor crystallites by ball milling can effectively increase the closed pores of hard carbon, because the small crystallites promote the formation of cross-linking between oxygen-containing functional groups. The present invention combines the alkaline activation method and the ball milling method to prepare anthracite-based hard carbon negative electrode sodium storage material with high first coulombic efficiency, which meets the commercial hard carbon demand (>90%).

[0072] For matters not mentioned above, the prior art applies.

[0073] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a coal-based hard carbon negative electrode sodium storage material, characterized in that: The steps include: S1. Using anthracite as a base material, activating it by an alkali activation method to obtain activated anthracite; S2, ball-milling the activated anthracite to obtain an anthracite precursor having a small crystallite size; S3. Carbonize the anthracite precursor at high temperature to obtain a coal-based hard carbon negative electrode sodium storage material.

2. The preparation method according to claim 1, characterized in that: The anthracite precursor La obtained in step S2 is 14-16 nm, and Lc is 0.8-0.95 nm.

3. The preparation method according to claim 1, characterized in that: The specific operation of step S1 is: fully mixing and grinding the anthracite with a strong alkali, then transferring the powder to air or nitrogen for pre-pyrolysis, and grinding the pre-pyrolysis product, then acid washing, water washing, suction filtering, and drying to obtain activated anthracite.

4. The preparation method according to claim 3, characterized in that: Step S1 also includes oxidizing the activated anthracite; the oxidation treatment operation is to place the activated anthracite in air for heating.

5. The preparation method according to claim 3, characterized in that: The pre-pyrolysis temperature is 200-400°C; and\or: the pre-pyrolysis temperature is 400°C.

6. The preparation method according to claim 3, characterized in that: Acid pickling is performed by stirring and immersing in hydrochloric acid or sulfuric acid with a concentration of 1 to 6 mol / L; washing with water until the pH is neutral.

7. The preparation method according to claim 1, characterized in that: In step S2, the ball milling is wet milling, with a rotation speed of 300-800 r / min, lasting for 4-12 hours, and a ball-to-material ratio of 200:

1.

8. The preparation method according to claim 1, characterized in that: In step S3, the high temperature carbonization temperature is 1000-2000°C, the time is 1-10 hours, and the heating rate is 1-5°C / min.

9. A coal-based hard carbon negative electrode sodium storage material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the coal-based hard carbon negative electrode sodium storage material as claimed in claim 9, characterized in that: Used as negative electrode material for sodium-ion batteries.

Citation Information

Patent Citations

  • Method for selectively regulating and controlling graphite-like crystallite sizes and interlayer spaces of heavy aromatic hydrocarbon hard carbon material

    CN110921646A

  • Hard carbon material and preparation method and application thereof

    CN115744874A

  • Negative electrode material, preparation method thereof and sodium ion battery

    CN117819525A

  • Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material

    CN118239487A

  • Carbon material for hybrid capacitor

    JP2016076673A

Cited By

  • Preparation method and application of semi-coke-based high-rate long-life hard carbon material

    CN119706806A

  • Method for preparing raw material of hard carbon negative electrode material from bituminous coal

    CN120504312A